FLORISTIC COMPOSITION AND WEED BIOMASS IN ORGANIC ALFALFA - ilic, olivera; nikolic, ljiljana m (Journal of Agricultural Sciences (Belgrade), 2016)
The paper presents the result of floristic composition and weed biomass in organic alfalfa crop in different years of alfalfa growing. The experiment was conducted in experimental plots in Futog, during the vegetation period 2015. It was noted the presence of 60 weed species,49 of all weeds was concluded in the third, 48 in the fourth and 34 in the fifth year oforganic alfalfa growing. Quantitative and qualitative structure of weed community was depend on the age of alfalfa crop. The analysis of covering values and the degree of presence of weed species can be seen that species: Rumex obtusifolius L., Taraxacum officinale Web., Cynodon dactylon Pers. and Artemisia vulgaris L. have the greatest significance on weed infestation of alfalfa. The largest number of weed species were belonged to the families Poaceae and Asteraceae. The biological spectrum of weeds species defined the terophyta dominance, whose number is reduced to the age of the crop, while the share of hemicryptophytes and geophytes more or less constant. Although we found a considerablelevel of infestation of alfalfa, alfalfa biomass has reached acceptable values that were significantly higher than the weed biomass, which was statistically highly significant.